American foreign relations reconsidered, 1890-1993 - Martel, Gordon (Taylor & Francis, 1994)
This major textbook brings together twelve of the leading scholars of US foreign relations. Each contributor provides a clear, concise summary of an important period or theme in US diplomatic and strategic affairs.